Avian Embryonic Culture: A Perspective of In Ovo to Ex Ovo and In Vitro Studies - Sukparangsi, Woranop; Thongphakdee, Ampika; Intarapat, Sittipon (Frontiers in Physiology, 2022)
Observation of avian embryos growing outside natural eggshell (ex ovo) has been done for so long since the early 19th century and since then chick embryonic structures are revealed reaching its in-depth view of external and internal anatomy, enabling us to understand conserved vertebrate development. However, the internal environment within eggshell (in ovo) still be the ideal place to perform various experiments to understand the nature of avian development and to apply for other biotechnology. With the advent of genetic manipulation and cell culture techniques, avian embryonic parts are dissected for explant culture to eventually generate expandable cell lines (in vitro cell culture). The expansion of embryonic cells allows us to unravel the transcriptional network for understanding pluripotency and differentiation mechanism in the embryos and in combination with stem cell technology facilitate the applications of avian culture to the next levels in transgenesis and wildlife conservation. In this review, we provide a panoramic view of the relationship among different cultivation platforms from in ovo studies to ex ovo as well as in vitro culture of cell lines with recent advances in the stem cell fields.